Answer:
Replace x with
![y^(1/4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6y3gpxbp5vn1xhp1pqkht71m7bn0hm7bjw.png)
Explanation:
The general form of a quadratic equation is
+ bx + c.
To find a substitution we have to think of a way of substituting ‘x’ to make it have a power of 2,
Here, we will use
-
+2 = 0
let x =
so it gives
(
)^8 – 3(
)^4 +2 = 0
– 3y + 2 = 0
Solving the equation
- 2y – y + 2 =0
(
– 2y) -1(y – 2) = 0
y(y - 2) -1(y - 2) = 0
(y-1) (y-2)
:- y = 1 or y = 2
Since x =
When y = 1
X =
X =
![4√(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/othkus6ghfhuqzxgh9f77g9igwducno6io.png)
X = 1
and when y = 2
X =
X =
![4√(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/4bjqo2m2scmttjj8t0sz357dyf1b7fxb01.png)
X = 1.1892...